Perceived Environmental and Health Impacts of Gas Flaring on Residents in Kwale Communities, Southern Nigeria - Ndinwa, Gabriel C. C; Akpafun, Solomon A; Chukumah, Charity O (Asian Journal of Energy Transformation and Conservation, 2020)
This study was designed to examine the perceived environmental effects of gas flaring and its associated health impact on residents in Kwale communities, Southern Nigeria. Three research objectives guided the study. Descriptive survey design and purposive sampling technique was adopted for the study. 750 household respondents from five different communities in Kwale axis were used for the study and an 18 item self-structured questionnaire was used to elicit information from the respondents. The instrument for data collection was administered to the respondents in the communities. The study revealed that gas flaring impact on the social, economic and environmental quality of the communities as 79.6% of the respondents positively affirmed the finding. A reasonable percentage (89.6%) of the sampled household respondents consent that gas flaring impact on the environmental activities as well as health of residents in the study area. Furthermore, 68% of the respondents confirm that gas flaring has a devastating effects on the vegetation and agricultural activities of the residents as some of them reported cases of stunted growth of crops, withered crop leaves, defoliation of plant and wrinkling of plant leaves. A higher percentage of respondents confirmed cases of critical gas flaring health related sick suffered by either themselves or family members and some of the respondents as well complained of excessive heat radiation and increase in temperature. Based on the findings, sustainable strategy for natural gas utilization was recommended in order to curtail the negative impacts and convert the excessive gas for economic and environmental benefits.